2015
DOI: 10.1590/1517-869220152106152116
|View full text |Cite
|
Sign up to set email alerts
|

Alongamento Intermitente E Contínuo Aumentam a Amplitude De Movimento E Reduzem a Força Dos Flexores De Punho

Abstract: REsUMOIntrodução: A manipulação do intervalo entre séries pode influenciar o desempenho de atividades subsequentes. Objetivo: Comparar o efeito do intervalo de alongamento estático de forma continua e intermitente no desempenho de flexores de punho. Métodos: A amostra foi composta por 14 adultos jovens, hígidos, do gênero masculino (idade 31±9 anos; estatura 178±0,7 cm; massa 85±12 Kg). Foi avaliada a amplitude de movimento passivo (ADMP) em extensão de punho, a força isométrica máxima de flexão de punho assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The muscle has an optimal length to generate maximum tension. As it is stretched or shortened beyond the optimal zone, the muscle progressively loses its ability to generate force [20][21][22]. Furthermore, many studies have already shown that increasing fat mass reduces exercise capacity [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The muscle has an optimal length to generate maximum tension. As it is stretched or shortened beyond the optimal zone, the muscle progressively loses its ability to generate force [20][21][22]. Furthermore, many studies have already shown that increasing fat mass reduces exercise capacity [23][24][25].…”
Section: Discussionmentioning
confidence: 99%